An Elaboration and Test of Framework of Constructive Deviance in Organizations - Abhijeet K. VADERA, (Institutional Knowledge at Singapore Management University, 2014)
Using multiple methods, we elaborated and tested a model of constructive deviance. In Study 1, we conducted a qualitative study with constructively deviant employees of a cement manufacturing firm in India to identify five factors which influenced these employees, namely, organizational justice, psychological empowerment, supervisor ethical leadership, supervisor openness, and moral identity. Next, we developed a model and proposed that organizational justice, moral identity, and psychological empowerment directly affect constructive deviance and that supervisor ethical leadership and supervisor openness would be positively related to psychological empowerment. Finally, we tested this framework using field data collected from 304 sales employee-supervisor dyads of a large multinational conglomerate in Malaysia and found support for our proposed model.